Packaging y marketing con causa: ¿Estamos comunicando de manera adecuada? - Sorribas Morales, Carolina (Pensar la Publicidad. Revista Internacional de Investigaciones Publicitarias, 2007)
In recent years, we are seeing a considerable increase of cause-related marketing programs carried out by companies and nonprofit organizations. Due to the increasing number of programs and to its relative innovation in Spain, many companies do not negotiate in an adequate manner the communication of this type of programs, especially concerning packaging Therefore they may damage the image of the companies in charge of them. This paper analyzes the information appeared in foodstuffs’ labels that have participated in cause-related marketing programs during October 2006 in Spain and reflects on its efficacy.